REVITALIZING ISLAMIC LEARNING: EXPLORING THE EFFECTIVENESS OF POWERPOINT IN IMPROVING STUDENT LEARNING ACHIEVEMENT - Adiyono, Adiyono; Rahayu, Arum Putri; Murni, Murni (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study is important to conduct with the aim of knowing the implementation and effect of using PowerPoint media on student learning outcomes. This learning media produces an active and focused atmosphere. This type of research is a pre-experimental design using a one-group pretest-posttest with a quantitative approach. The research population used 36 students of class XI Software and Game Development (PPLG) 1 SMK Negeri 1 Tanah Grogot. Data collection techniques in the form of tests and non-tests, data analysis techniques using validity test, reliability test, normality test, Z test and N-Gain. The conclusion is that there is an implementation of PowerPoint media on student learning outcomes in Islamic Religious Education class XI SMK Negeri 1 Tanah Grogot with an N-Gain increase value of 0.8317 or equivalent to 83% of the high category. There is an effect of increasing the use of PowerPoint media on student learning outcomes in Islamic Religious Education class XI SMK Negeri 1 Tanah Grogot with Zcount 0.189 < Ztabel 1.96. For further researchers, it is expected to examine more sources and references used related to the effect of using PowerPoint media on student learning outcomes so that the research can be better and more complete, further researchers can also develop research by examining the latest version of PowerPoint as a material consideration to further deepen further research either on other subjects or on other aspects.